Porphyry Related Skarn Mineralization within Calc - Silicate Rocks in the Batu Hijau Deposit, Sumbawa Island, Indonesia - , M. T. Aye ([Yogyakarta] : Departments of Geological Engineering,Facultyof, 2009)
A world-class porphyry copper-gold deposit, Batu Hijau is situated at the southwestern part of Sumbawa Island and lies along the active eastwest trending Sunda-Banda magmatic arc , Indonesia. The mineable reserve of the deposit is 9/4 million metric tonnes at the grade of 0.525% Cu and 0.403 g/t Au. Several intervals of skarn mineralization with calc-silicate minerals were also found at the deeper level of the deposit by a drilling program in 2003 by Newmont. Most of the skarn mineralizing zones are present in the andesitic volcanic lithic breccias (Middle to Late Miocene), along its contact with copper-gold bearing tonalite porphyry intrusion. Green, reddish-brown, locally black colored, finegrained, granular and banding natures are the typical characteristics of calc-silicate minerals in this deposit. The calc-silicate rocks are mainly composed of garnet and pyroxene with minor amount of calcite, zeolite, quartz, epidote and chlorite. The ore mineralization is closely related with massive magnetite and disseminated pyrite and chalcopyrite and the copper - gold content is especially rich in brecciated and broken magnetite zone that is along the contact between tonalite and calc-silicate rocks. The presence of garnet and clinopyroxene represents the prograde stage while the calcite, zeolite, epidote and quartz the retrograde stage of skarn mineralization. Moreover according to the fluid inclusion study (Idrus et aI., 2008), the skarn mineralization occurred at high temperature of 340 - &gt